2021
DOI: 10.1038/s41368-021-00128-2
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke promotes oral leukoplakia via regulating glutamine metabolism and M2 polarization of macrophage

Abstract: Oral immunosuppression caused by smoking creates a microenvironment to promote the occurrence and development of oral mucosa precancerous lesions. This study aimed to investigate the role of metabolism and macrophage polarization in cigarette-promoting oral leukoplakia. The effects of cigarette smoke extract (CSE) on macrophage polarization and metabolism were studied in vivo and in vitro. The polarity of macrophages was detected by flow cytometric analysis and qPCR. Liquid chromatography-mass spectrometry (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…In addition, linking environmental risk factors with TAM phenotypes in OPLs, Zhu et al. demonstrated that cigarette smoke extract increased M2 macrophage OPL infiltration and polarization, increased immunosuppressive cytokines including arginase-1 and IL-10 and decreased pro-inflammatory markers TNFα and iNOS ( 45 ). Furthermore, this group proposed that smoking activated glutamine transport and metabolism in TAM to promote epithelial proliferation and inhibit apoptosis.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“…In addition, linking environmental risk factors with TAM phenotypes in OPLs, Zhu et al. demonstrated that cigarette smoke extract increased M2 macrophage OPL infiltration and polarization, increased immunosuppressive cytokines including arginase-1 and IL-10 and decreased pro-inflammatory markers TNFα and iNOS ( 45 ). Furthermore, this group proposed that smoking activated glutamine transport and metabolism in TAM to promote epithelial proliferation and inhibit apoptosis.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“…A presence of immune‐inflammation gene signature was also reported in prostate tumors of smokers (Prueitt et al, 2016). Another study demonstrated that cigarette smoke extract (CSE) promoted oral leukoplakia via regulating glutamine metabolism and M2 polarization of macrophages (Zhu et al, 2021). CSE was also shown to impair the ability of monocyte‐derived and alveolar macrophages to limit mycobacterial growth (van Zyl‐Smit et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PMDB database was used for qualitative analysis, and specific procedures were based on studies by Li et al, 2020 , Wu et al, 2022 . The quantitative analysis was performed with reference to Cao et al, 2020 , Zhu et al, 2021 .…”
Section: Methodsmentioning
confidence: 99%